Evaluation of polypropylene degradation with commercial additives in different media of exposure - Pires, Jéssica Pereira; Ramos, Alessandro da Silva; Miranda, Gabriela Messias; Ligabue, Rosane Angélica; Lima, Jeane Estela Ayres de; Lourega, Rogerio Vescia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Polypropylene (PP) is one of the most widely used polymers in the world, mainly due to its versatility, good properties, and low cost. However, since it is not easily degraded in the natural environment, several research projects have been developed to increase its biodegradability. The use of pro-degrading additives has been explored, as they promote the process of polymer degradation. Nevertheless, few studies have evaluated the degradation of these materials in natural aqueous environments such as rivers and lakes, which contain large amounts of PP waste. The goal of this study was to evaluate the degradation of polypropylene, as well as the biodegradation of PP through the incorporation of two additives of different natures, organic and enzymatic. For this purpose, PP blends were produced with 4% additive, which has the purpose of conferring biodegradability to the material, since polypropylene has high resistance to degradation. In order to verify the behavior of the materials against degradation tests with 2 different media (saline and fresh water) for a period of 6 months, the samples were characterized by Fourier Transformed Infrared Spectroscopy and Field emission scanning electron microscopy. The characterizations were carried out in order to verify the changes in the structural characteristics and in the morphology of the materials caused by the incorporation of the additive and by the exposure to the degradation media. From the results obtained, it was observed that the additives influenced the degradation of PP. In addition, the enzyme additive and the saline media caused more significant changes in the properties analyzed, indicating greater influence on the degradation process. It was concluded that the incorporation of commercial additives gives biodegradable properties to PP. Therefore, this study has an important role in the research and development of biodegradable materials in order to minimize the effects caused by plastic waste in the environment. Thus, the studied materials are an alternative in the field of plastic packaging, reducing the effects caused by plastic waste in the environment.